A Novel NMDA Receptor Antagonist Protects against Cognitive Decline Presented by Senescent Mice - Júlia Companys-Alemany; Andreea L. Turcu; Aina Bellver-Sanchis; Maria I Loza; José M. Brea; Anna M Canudas; Rosana Leiva; Santiago Vázquez; Mercè Pallàs; Christian Griñán-Ferré (MDPI AG, 2020)
Alzheimer’s disease (AD) is the leading cause of dementia. Non-competitive N-Methyl-D-aspartate (NMDA) receptor antagonist memantine improved cognition and molecular alterations after preclinical treatment. Nevertheless, clinical results are discouraging. In vivo efficacy of the RL-208, a new NMDA receptor blocker described recently, with favourable pharmacokinetic properties was evaluated in Senescence accelerated mice prone 8 (SAMP8), a mice model of late-onset AD (LOAD). Oral administration of RL-208 improved cognitive performance assessed by using the three chamber test (TCT), novel object recognition test (NORT), and object location test (OLT). Consistent with behavioural results, RL-208 treated-mice groups significantly changed NMDAR2B phosphorylation state levels but not NMDAR2A. Calpain-1 and Caspase-3 activity was reduced, whereas B-cell lymphoma-2 (BCL-2) levels increased, indicating reduced apoptosis in RL-208 treated SAMP8. Superoxide Dismutase 1 (SOD1) and Glutathione Peroxidase 1 (GPX1), as well as a reduction of hydrogen peroxide (H2O2), was also determined in RL-208 mice. RL-208 treatment induced an increase in mature brain-derived neurotrophic factor (mBDNF), prevented Tropomyosin-related kinase B full-length (TrkB-FL) cleavage, increased protein levels of Synaptophysin (SYN) and Postsynaptic density protein 95 (PSD95). In whole, these results point out to an improvement in synaptic plasticity. Remarkably, RL-208 also decreased the protein levels of Cyclin-Dependent Kinase 5 (CDK5), as well as p25/p35 ratio, indicating a reduction in kinase activity of CDK5/p25 complex. Consequently, lower levels of hyperphosphorylated Tau (p-Tau) were found. In sum, these results demonstrate the neuroprotectant role of RL-208 through NMDAR blockade.